O planejamento estratégico: um estudo em uma organização civil do Rio Grande do Sul - Postingher, Paulo Sérgio (Universidade do Vale do Rio dos Sinos, 2014)
This paper aims to describe the implementation process of strategic planning at the Centro de Educação Profissional São João Calábria, a nonprofit organization in Porto Alegre, Rio Grande do Sul, according to the perspective of its key managers. Besides analyzing this implementation process, it also seeks to show the results from it. For this research we analyzed the process of adopting the technique of strategic planning, highlighting its motivation, its way of implementation, the level of decisional participation of the non-managing members in this process, the strategy applied to guide the typical social actions of the third sector in this professional and voluntary institution, and we also evaluated the results achieved by the organization after the implementation of the strategic planning process. A literature review was conducted on strategy, strategic management, strategic planning and its implementation. The research consists of a case study with qualitative methodology applied to conduct a descriptive field study, since its aim is to verify the planning and strategy adopted and implemented in the perspective of managers of this organization. We interviewed seven members of the Operational Management Team in the organization, one manager of Congregação dos Pobres Servos da Divina Providência (Congregation of the Poor Servants of the Divine Providence) and five other subjects involved in the operational and support activities. The results show that planning has brought many benefits and growth to the organization over the past decade, since it was implemented. The results also revealed that, despite the growth, there are some gaps that need to be improved to improve the lives of both employees and beneficiaries. This study helped to have a different view of third sector organizations, which are often averse to planning and management tools, because managers misunderstand social issues and survival, forgetting to plan and think about their strategies.
Keywords: Planejamento estratégico; Gestão estratégica; Estratégia; Planejamento estratégico em organizações sem fins lucrativos; Strategic planning; Strategic management; Strategy; Strategic planning in nonprofit organizations; ACCNPQ::Ciências Sociais Aplicadas::Administração